Belly dancer female impersonator - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows female impersonator dressed as a belly dancer lying on the floor on her side. Her right arm is held up into the air, her left arm props up her upper body and a sword balances on her head. Behind her is a fireplace decorated with Christmas stockings.